2020
DOI: 10.1186/s12884-020-03410-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Robson classification to understand the increased risk of cesarean section in case of maternal obesity

Abstract: Background The aim of this study was to identify characteristics of pregnant women with obesity that contribute to increased cesarean rate. Methods Retrospective cohort in a single academic institution between 2012 and 2019. Women who delivered during this period were classified according to the Robson classification. Women with normal body mass index (N = 11,797) and with obesity (N = 2991) were compared. The contribution of each Robson group to the overall caesarean rate were compared. Results The overall … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“… 27 A recent French study reported a higher rate of CS in women with (28.1%) than without (14.2%) obesity, largely explained by those in Robson Group 5. 28 In the current study, we took into account similar factors, suggesting that maternal age, obesity, comorbidities and certain obstetrical complications do not completely explain the higher rate of CS observed in women with infertility.…”
Section: Discussionmentioning
confidence: 99%
“… 27 A recent French study reported a higher rate of CS in women with (28.1%) than without (14.2%) obesity, largely explained by those in Robson Group 5. 28 In the current study, we took into account similar factors, suggesting that maternal age, obesity, comorbidities and certain obstetrical complications do not completely explain the higher rate of CS observed in women with infertility.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to underline that among CS indications there is not maternal obesity condition 3. Maternal obesity is a major health issue in most of the industrialised countries and the increasing rate of obesity among pregnant women has also increased studies about the correlation between maternal obesity and pregnancy complications such as hypertensive disorders, gestational diabetes and macrosomia4; moreover, a meta-analysis has reported an increased risk of caesarean delivery among overweight or obese women 5.…”
Section: Commentarymentioning
confidence: 99%
“…Obesity and excessive gestational weight gain similarly increase risks of caesarean delivery, preterm birth < 37 gestational weeks, and the rates of large-or small-for-gestational-age (LGA or SGA) infants, defined by a birthweight ≥ 90 th , respectively < 10 th centile of the referred population. Thus, we defined these outcomes as secondary outcomes in addition to neonatal birthweight in total [20,21].…”
Section: Secondary Outcomesmentioning
confidence: 99%